Mediterranean Diet as a Supportive Intervention in Cancer Patients: Current Evidence and Future Directions - Roberta Rubino; Michela Rosaria Iuliucci; Simona Gatani; Arianna Piscosquito; Bruno D’Ambrosio; Concetta Ingenito; Luca Scafuri; Carlo Buonerba; Giuseppe Di Lorenzo (Current Oncology, 2022)
Cancer currently represents a leading cause of morbidity and mortality, and it can be held responsible for about one in six deaths worldwide [...]